Analisis Kualitatif Pemecahan Masalah dan Ketergantungan Kognitif Mahasiswa Calon Guru dalam Penggunaan Generative AI - Ferdinanda, Thierry; Dewi, Tiara Anggia; Budiono, Desi (Jurnal Simki Pedagogia, 2026)
This qualitative descriptive study analyzes Generative Artificial Intelligence (GenAI) usage patterns and their impact on pre-service teachers' problem-solving capabilities through Polya’s framework. Data from ten informants were analyzed using the Miles and Huberman model. Findings reveal that GenAI serves as effective "cognitive scaffolding" during the understanding and planning phases. However, a "dependency paradox" emerged during execution, while the evaluation phase showed critical literacy deficiencies due to automation bias. The study concludes that uncontrolled GenAI use jeopardizes students' procedural skills and epistemic agency. It recommends reorienting curricula toward Critical AI Literacy and AI-TPACK frameworks to safeguard intellectual autonomy.